Measurement of isocenter accuracy and image distortion in magnetic resonance-guided radiotherapy - Dorsch, Stefan (2020)
Magnetic resonance (MR)-guided radiotherapy involves complex irradiation- and imaging devices (MR-Linacs), as well as complex treatment procedures. To assure accurate patient treatments, both have to be tested for proper functioning. Here, new methods to simultane-ously measure the isocenter alignment accuracy and the geometric image distortions of clin-ical MR-Linacs were developed. A new phantom was designed, which includes a polymer dosimetry gel-container to visualize the beams from a star shot and to identify the radiation isocenter position in MR as well as a regular grid used to visualize the MR image distortions in 3D. It was found that the gel can be evaluated immediately after irradiation with a geo-metric accuracy comparable to that of radiochromic films. The method was applied on a clinical 0.35 T MR-Linac and the isocenter alignment accuracy in 3D was found to be (0.8 ± 0.9) mm. The spatial image distortions after machine-specific correction were (0.60 ± 0.28) mm and 99.82% of the 1330 evaluated control points within a 140 mm sphere had devi-ations below 1.5 mm. Finally, a 3D printing materials and printing technique, compatible with the polymer dosimetry gel, was identified for future designs of anthropomorphic phantoms to be used in end-to-end tests in MR-guided radiotherapy.
Keywords: Hochschulschrift